Bidirectional All‐Optical Synapses Based on a 2D Bi2O2Se/Graphene Hybrid Structure for Multifunctional Optoelectronics. (28th May 2020) - Yang, Chia‐Ming; Chen, Tsung‐Cheng; Verma, Dharmendra; Li, Lain‐Jong; Liu, Bo; Chang, Wen‐Hao; Lai, Chao‐Sung
Abstract: Neuromorphic computing has been extensively studied to mimic the brain functions of perception, learning, and memory because it may overcome the von Neumann bottleneck. Here, with the light‐induced bidirectional photoresponse of the proposed Bi2 O2 Se/graphene hybrid structure, its potential use in next‐generation neuromorphic hardware is examined with three distinct optoelectronic applications. First, a photodetector based on a Bi2 O2 Se/graphene hybrid structure presents positive and negative photoresponsibility of 88 and −110 A W −1 achieved by the excitation of visible wavelength and ultraviolet wavelength light at intensities of 1.2 and 0.3 mW cm −2, respectively. Second, this unique photoresponse contributes to the realization of all optically stimulated long‐term potentiation or long‐term depression to mimic synaptic short‐term plasticity and long‐term plasticity, which are attributed to the combined effect of photoconductivity, bolometric, and photoinduced desorption. Third, the devices are applied to perform digital logic functions, such as "AND" and "OR, " using full light modulation. The proposed Bi2 O2 Se/graphene‐based optoelectronic device represents an innovative and efficient building block for the development of future multifunctional artificial neuromorphic systems. Abstract : All‐optical synapses based on a 2D Bi2 O2 Se/graphene hybrid structure can yield positive photoresponses under visible light and negative photoresponses under 365 nm illumination without the extra electrical control. Contributing to this unique optoelectronic property, the single two‐terminal device with fully optical operations is demonstrated for the photodetector, optoelectronic synapses, and optical logic functions.